Comparison Between Vascular Plasminogen Activator Activity and Changes in Blood Flow in the Renal Cortex in Pigs - Smokovitis, Athanasios; Maier, Manfred; Binder, Bernd R (Thrombosis and Haemostasis, 1984)
Patterns of vascular plasminogen activator activity (PAA) and of blood flow were compared in the renal cortex of pigs. The comparison was made in pigs with or without induction of hemorrhagic hypotension and continuous infusion of indomethacin (prostaglandin synthetase inhibitor) or saralasin (competitive inhibitor of angiotensin II). Blood flow was measured by radiolabelled microspheres. A significant decrease in the vascular PAA was observed only in saralasin treated animals (15% in not hemorrhaged pigs and 30% in the inner and 45% in the outer half of the renal cortex in hemorrhaged pigs). Changes in plasmin inhibitor activity in the renal cortex were not noted. No correlation could be seen between vascular PAA and changes in blood flow in the renal cortex or changes in the mean arterial blood pressure. The vascular fibrinolytic response to saralasin should be due to an effect of saralasin independent of the changes in blood flow induced by this agent.
Keywords: Blood flow; Renal cortex; Fibrinolysis; Indomethacin; Saralasin